2019
DOI: 10.1080/09168451.2018.1562879
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an internal cavity in the PhoQ sensor domain for PhoQ activity and SafA-mediated control

Abstract: The PhoQ/PhoP two-component signal transduction system is conserved in various Gram-negative bacteria and is often involved in the expression of virulence in pathogens. The small inner membrane protein SafA activates PhoQ in Escherichia coli independently from other known signals that control PhoQ activity. We have previously shown that SafA directly interacts with the sensor domain of the periplasmic region of PhoQ (PhoQ-SD) for activation, and that a D179R mutation in PhoQ-SD attenuates PhoQ activation by Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…For example, the change in transcriptional response in PhoQ is modest, reaching about a factor of 5–20-fold change, while other two-component systems such as VirA have a dynamic range as large as 10 5 ( Wang et al, 2015 ; Baruah et al, 2004 ; Eguchi and Utsumi, 2014 ; Gao and Lynn, 2005 ). It is however possible that combinatorial signals might further increase the overall kinase activity of PhoQ from that observed at low Mg 2+ , owing to additive modulation of the sensor domain by other stimuli H + , antimicrobial peptides, MgrB, SafA, UgtL Yoshitani et al, 2019 , as some independence between signal inputs has been demonstrated for S. Typhimurium PhoQ ( Hicks et al, 2015 ). For simple systems that respond to a single ligand, the maximal response is defined by the ratio of the intrinsic affinities of the ligand for the ‘kinase-on’ versus ‘kinase-off’ conformations (K dON /K dOFF ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, the change in transcriptional response in PhoQ is modest, reaching about a factor of 5–20-fold change, while other two-component systems such as VirA have a dynamic range as large as 10 5 ( Wang et al, 2015 ; Baruah et al, 2004 ; Eguchi and Utsumi, 2014 ; Gao and Lynn, 2005 ). It is however possible that combinatorial signals might further increase the overall kinase activity of PhoQ from that observed at low Mg 2+ , owing to additive modulation of the sensor domain by other stimuli H + , antimicrobial peptides, MgrB, SafA, UgtL Yoshitani et al, 2019 , as some independence between signal inputs has been demonstrated for S. Typhimurium PhoQ ( Hicks et al, 2015 ). For simple systems that respond to a single ligand, the maximal response is defined by the ratio of the intrinsic affinities of the ligand for the ‘kinase-on’ versus ‘kinase-off’ conformations (K dON /K dOFF ).…”
Section: Resultsmentioning
confidence: 99%
“…Still, it is worth noting that PmrB H61 is immediately adjacent to a conserved glutamate essential for pH sensing in the Salmonella homolog (Perez and Groisman, 2007). Also, I88 is in the vicinity of P83, essential for SafA binding and PhoQ activation in E. coli (Yoshitani et al, 2019). HK853 K387 is equivalent to PhoQ E397, substituted by a glycine in one of the isolates.…”
Section: Chromosomal Mutations Associated With Colistin Resistancementioning
confidence: 99%
“…5A) shows that genes phoQ, phoP, rpoS and katE were significantly upregulated under heat and solar photothermal stress, and rpoS and katE expression were the highest under heat stress, followed by photothermal disinfection. SafA connects the EvgS/EvgA and PhoQ/PhoP systems and activates the PhoQ/PhoP system by interacting with the periplasmic region of PhoQ directly 44 and enhancing histidine kinase autophosphorylation. 45 The PhoQ/PhoP system prohibits the degradation of sigma factor RpoS, which is a regulatory factor of oxidative stress, through upregulating katE (encoding catalase) expression 46 and downregulating genes involved in the entire tricarboxylic acid (TCA) cycle.…”
Section: The Molecular Mechanism Of Bacterial Inactivation By Solar P...mentioning
confidence: 99%